Live CCTV Monitoring as a Crime Prevention Method: A Case Study of Prayer Rooms at Station X and Z - Setiawan, Sapta Rizki; Olii, Mohammad Irvan (Jurnal Kriminologi Indonesia, 2026)
Abstract. The use of Closed-Circuit Television (CCTV) technology in security systems is often passive in nature, functioning mainly as a tool for documentation and post-incident evidence collection. This article presents a case study of successful active live surveillance conducted by security personnel at the Security Operation Center of a private security company in prayer rooms (mushola) of Stations X and Z. Through 24/7 CCTV monitoring and real-time voice intervention using integrated loudspeakers, significant changes were observed in preventing theft of personal belongings of visitors during prayer. Employing a case study approach with autoethnographic methods, this research involved interviews with the management of PT XZ and Security Console Operator from PT GA, along with field observations. Findings demonstrate that this active surveillance model effectively eliminated theft incidents. This article advocates for a paradigm shift in the utilization of CCTV—from a passive recording device to an active deterrent tool based on immediate intervention.